Sutureless and glue free conjunctival auto grafting after pterygium excision - Goswami, M.K.; Asaduzzaman, Md (IMC Journal of Medical Science, 2017)
Background and objectives: Suture or glue has been used to secure the conjunctival auto graft after excision of the pterygium. Recently, auto grafting using patients own blood as a bioadhesive to secure the graft in position has been described by several authors. Therefore, the present study was undertaken to determine the outcome of excision of pterygium and sutureless conjunctival auto graft using patients own blood as a bioadhesive. Methods: Patients with primary and recurrent pterygium attending the Department of Ophthalmology of Bangladesh Institute of Research, Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) hospital from March 2014 to July 2015 were included in the study. Pterygium was excised and conjunctival auto graft was applied. Grafts were secured to the pterygium excision area with auto blood fibrin clot. All patients were examined after 48 hr and followed for 1, 4 and 12 weeks for graft dislodgement, sub-conjunctival hemorrhage, graft recession, graft edema and recurrence of pterygium. Results: A total of 35 primary and 2 recurrent pterygium cases were included in the study. The mean operation time was 15±1 minutes. Out of 37 eyes 5 (13.5%) had subconjunctival hemorrhage and 2 (5.4%) had graft recession and edema after 48hrs of operation. At 3 months follow up, 2 cases (5.4%) of graft recession and no case of recurrence of pterygium was found. Conclusion: Pterygium excision and conjunctival auto graft without sutures appears to be an effective treatment modality for primary and recurrent pterygium with no additional cost. IMC J Med Sci 2016; 10(2): 36-38